Dual frequency integrated antenna (DFIA) with image rejection - Widad, Ismail; Sohiful Anuar, Zainol Murad (Institute of Electrical and Electronics Engineers (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org